A CASE OF OCCIPITAL MENINGOENCEPHALOCYSTOCELE IN A FULLTERM NEONATE - Jalaluddin, Syatirah; Saharuddin, Saharuddin (Alami Journal (Alauddin Islamic Medical) Journal, 2019)
Background:The neural tube defect is one of the congenital anomalies which is frequently found in developing countries. A large occipital meningoencephalocystocele possess difficulties in surgical intervention, because the sac usually contains large amounts of cerebrospinal fluid, meninges, brain tissue, and, a higher rate of surgical complications, as well as a difficult positioning at intubation to minimalize the complications. Case Presentation:To report a case of neonate with a large occipital meningoencephalocystocele, which was managed with surgery by removing the extra cranial tissue containing the necrotic brain tissue and the meninges. The patient was discharge with normal wound healing, but ventriculoperitoneal shunt was not performed. Feeding difficulties and poor growth were observed several months after surgery with obvious neurological problems. Conclusions:A through management of meningoencephalocystocele involves many aspects include treatment after surgery was performed.